IMPLEMENTASI SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) DALAM MEMFASILITASI KERUMAHTANGGAAN BIRO UMUM SEKRETARIAT DAERAH PROVINSI JAWA TIMUR - Setiawan, Defanio Azriel; Anisykurlillah, Rosyidatuzzahro (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
The Regional Government Information System (SIPD) is an e-government system with a program or network that is used to harmonize coordination between the central government and regional governments. The Regional Government Information System (SIPD) has been regulated in Minister of Home Affairs Regulation Number 70 of 2019 where the system is designed to be more responsive, adaptive, innovative, dynamic and accountable. SIPD was designed by the Ministry of Home Affairs to harmonize the flow of stages in structuring regional plan documents based on statutory regulations. The aim of this research is to determine the implementation of SIPD in facilitating housekeeping at the General Bureau of the Regional Secretariat of East Java Province. The research method used is a qualitative descriptive approach. Data collection techniques were carried out through observation, interviews, literature study and documentation. The findings in this research use the concept of policy implementation according to Edwards III by reviewing several aspects such as communication, resources, disposition and bureaucratic structure. In general, the implementation of SIPD has gone quite well and effectively. However, there are still several obstacles in its implementation which have not been carried out optimally. Some of these obstacles are a lack of time efficiency in carrying out tasks and a lack of information in solving problems due to a lack of socialization and information related to SIPD. Therefore, there needs to be clarity regarding support and coordination with other agencies so that the implementation process runs well. This is related to increasing the quantity of human resources to support effectiveness and time efficiency in completing tasks. Keywords: General Bureau; Implementation; SIPD